2023
DOI: 10.1051/e3sconf/202337101011
|View full text |Cite
|
Sign up to set email alerts
|

Integrating spatial database for predicting soil salinity using machine learning methods in Syrdarya Province, Uzbekistan

Abstract: Soil salinization of irrigated lands is a global problem in providing the necessary food and feed to meet the needs of a growing world population. Salinization in arid and semiarid areas can occur when the water table is three and more meters above the soil surface. Nowadays, innovative technologies are widely implemented in agriculture to increase yields and monitor changes in any area timely. Advanced technologies such as remote sensing (R.S.) data have become an economically efficient tool for assessing, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Their findings indicated that the XGB regression model exhibited the most favorable performance, achieving coefficients of determination of up to 0.701. Muratov et al [35] integrated four machine learning techniques-Gaussian mixture model (GMM), RF, support vector machine (SVM), and K-nearest neighbors (KNN)with remote sensing technology in their study to enhance the precision of soil salinity monitoring. Wang et al [36] employed Sentinel-1A synthetic aperture radar (SAR) imagery along with machine learning algorithms, including RFR, multiple linear regression (MLR), and support vector regression (SVR), for investigating variations in soil moisture and salinity.…”
Section: Comparison and Optimization Of Soil Salinity Inversion Modelsmentioning
confidence: 99%
“…Their findings indicated that the XGB regression model exhibited the most favorable performance, achieving coefficients of determination of up to 0.701. Muratov et al [35] integrated four machine learning techniques-Gaussian mixture model (GMM), RF, support vector machine (SVM), and K-nearest neighbors (KNN)with remote sensing technology in their study to enhance the precision of soil salinity monitoring. Wang et al [36] employed Sentinel-1A synthetic aperture radar (SAR) imagery along with machine learning algorithms, including RFR, multiple linear regression (MLR), and support vector regression (SVR), for investigating variations in soil moisture and salinity.…”
Section: Comparison and Optimization Of Soil Salinity Inversion Modelsmentioning
confidence: 99%